Inuit and modern hunter-gatherer subsistence - Wenzel, George (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2013)
AbstractSome two decades ago, Asen Balikci (1989) and David Riches (1990) questioned whether research on Inuit, despite production of a voluminous literature, had made any contribution to theoretical issues in anthropology. On their heels, Burch (1994) asked very much the same about Hunter-Gatherer Studies. The thesis of the present paper is that research on Inuit economy has, in fact, contributed importantly to a rethinking of the shape and content of subsistence. Once described as encompassing the most basic economic activities, it is now understood as a cultural adaptation. This has import because few hunter-gatherer societies can be portrayed as they were at the time of the Man the Hunter symposium (Lee and DeVore 1968). Rather, today, hunter-gatherers, from the Arctic to Australia, experience near-constant contact with market economies and a reality in which money plays a critical part in their livelihoods. It is in this regard that research on Inuit, as noted by Sahlins (1999), has conceptually contributed both to Hunter-Gatherer Studies and to anthropology.